High-Intensity CsPbBr3 Perovskite LED using Poly(bis(4-phenyl)(2, 4, 6-trimethylphenyl)amine) as Hole Transport and Electron-Blocking Layer. (2020) - Simkus, Gintautas; Sanders, Simon; Stümmler, Dominik; Vescan, Andrei; Kalisch, Holger; Heuken, Michael
Abstract: The majority of highly efficient perovskite light-emitting diodes (PeLED) contain PEDOT:PSS (poly(3, 4-ethylenedioxythiophene):polystyrenesulfonate) as hole transport layer (HTL). However, the hygroscopic and acidic nature of PEDOT:PSS may lead to deterioration of PeLED performance. Moreover, due to its inferior electron-blocking properties, an additional electron-blocking layer (EBL) is required to establish charge balance and consequently obtain superior emission characteristics in typically electron-rich PeLED structures. In this work, PTAA (poly(bis(4-phenyl)(2, 4, 6-trimethylphenyl)amine)) serving both as HTL and EBL is employed to substitute PEDOT:PSS in PeLED. The perovskite CsPbBr3 is chosen as emissive layer (EML) material due to its high color purity and photoluminescence (PL) quantum yield. Dense CsPbBr3 films are fabricated on PTAA-coated ITO substrates by employing a one-step spin-coating approach based on nonstoichiometric perovskite precursor solutions. To suppress non-radiative recombination, a small amount of methylammonium bromide (MABr) is incorporated in the CsPbBr3 lattice. The resulting films exhibit excellent coverage and PL intensity. PeLED containing pure CsPbBr3 films as EML show a green emission with a peak at 520 nm, maximum luminance of 11, 000 cd/m 2, an external quantum efficiency (EQE) of 3.3 % and a current efficiency (CE) of 10.3 cd/A. Further enhancement to 21, 000 cd/m 2, 7.5 % and 27.0 cd/A is demonstrated by PeLED with MABr-doped CsPbBr3 layers.